PSO-Based PI Controller for Speed Control Of DC Motor - Abd Samat A.A.; Subani M.A.; Ab Aziz N.F.; Salim N.A.; Daud K.; Tajudin A.I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Controllers; DC motors; Electric loads; Electric machine control; Particle swarm optimization (PSO); Timing circuits; Transient analysis; Tuning; Two term control systems; Armature voltage control; D.C. motors; DC chopper circuit; DC choppers; Error methods; Particle swarm; Particle swarm optimization; Proportional integral controllers; Separately excited dc motors; Swarm optimization; Choppers (circuits)